Regulatory mechanisms of blood lactate production during exercise in man. - Palma, M. S.; Kokubun, E.; Sibuya, C. Y.; Santos, J. W.; Freire, P. M. (My University, 1989)
During cycloergometric exercise at progressively increasing loads, blood lactate concentration increased about 12-fold. Pyruvate concentration decreased initially (for loads of 50-75 W), increased with loads of 75 to 125 W and then decreased again until the end of exercise. The malate concentration increased abruptly between 50 and 75 W, followed by a slow decline; citrate increased about nine-fold as the exercise load was increased to 125 W and then fell sharply. Thus, the production of lactate during low-intensity exercise seems to occur by the mass-action effect caused by enhanced glycolysis, whereas with moderate loads the glycolysis rate is very much reduced and most of the lactate production seems to involve the action of the malate-aspartate shuttle. For high-intensity exercise, both mechanisms appear to participate in lactate production.